Clinical, Hematological And Inflammatory Markers Profile In COVID-19 Patients At Tertiary Care Centre (Journal of Pharmaceutical Negative Results, 2022)
Background: The ongoing pandemic of severe acute respiratory syndrome by coronavirus-2 (SARS-CoV-2) continues to pose severaldiagnostic and therapeutic challenges. Assessing clinical, demographic, biochemical, haematological and inflammatory parameters havethus become important for investigating the COVID-19 cases.Materials and Methods: A total of 505 Covid-19 positive cases were included in this study to compare their haematological, biochemicaland inflammatory parameters among mild, moderate and severe cases who were categorized as per ICMR guidelines and Institute guidelines.Results: In our study 54% patients belonged to >50 years of age group. Different Haematological values were studied for statisticalsignificance where White blood cell count (WBC), Neutrophil count, Neutrophil lymphocyte ratio (NLR), Absolute neutrophil count (ANC),Lymphocyte count and Absolute lymphocyte count (ALC) showed statistical significance with p value <0.05. Among inflammatory markersC-reactive protein (CRP), coagulative marker D-Dimer and biochemical parameters such as S.Ferritin and lactate dehydrogenase (LDH)levels showed statistical significance with p value <0.05.There was no significant change in the Hemoglobin, Monocyte, Absolute monocytecount (AMC), Lymphocyte monocyte ratio (LMR) and platelet count.Conclusion: According to the findings of our study, WBC, neutrophil, lymphocyte, neutrophil lymphocyte ratio, CRP, D-dimer, LDH andserum ferritin played an essential part in risk stratification models that serves as clinical predictors of severity in COVID-19 patients.